1988
DOI: 10.1111/j.1399-3054.1988.tb00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought effects on photosynthesis and fluorescence in hard wheat cultivars grown in the field

Abstract: Net photosynthesis of the flag leaf of hard wheat (Triticum durum L. evs Valforte, Produra, Adamello, Karel, Appulo and El Amel from the collection of the Instituto di Cerealicultura. Foggia, Italy) of different water potential has been studied on three consecutive years. Net photosynthesis was measured in natural conditions with a LI‐COR portable instrument and in saturating CO2 with an oxygen electrode. Net photosynthesis and stomatal conductance were significantly lower in the unirrigated leaves. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 13 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…It can be inferred from these observations that marked decreases of potential PS II activity may occur only during periods of complete cessation of assimilation and under intense irradiance. As the observed decreases resulted from both increased F 0 and decreased F m , it can be concluded that they were the expression of some kind of damage to the PS II (Demmig and Björkman, 1987 (Ben et al, 1987;Genty et al, 1987;Di Marco et al, 1988 ; 2) an increasing part of the electron flow originating from PS II may be diverted from carboxylation to photorespiration, as experimentally demonstrated by Comic and Briantais (1991 Epron and Dreyer, 1990). In our case, high light favored an alteration in PS II reaction centers, as the reduction in F v /F m resulted from both a decrease in F m and an increase in F 0 (Demmig and Björkman, 1987).…”
Section: Gas-exchange Measurementsmentioning
confidence: 72%
“…It can be inferred from these observations that marked decreases of potential PS II activity may occur only during periods of complete cessation of assimilation and under intense irradiance. As the observed decreases resulted from both increased F 0 and decreased F m , it can be concluded that they were the expression of some kind of damage to the PS II (Demmig and Björkman, 1987 (Ben et al, 1987;Genty et al, 1987;Di Marco et al, 1988 ; 2) an increasing part of the electron flow originating from PS II may be diverted from carboxylation to photorespiration, as experimentally demonstrated by Comic and Briantais (1991 Epron and Dreyer, 1990). In our case, high light favored an alteration in PS II reaction centers, as the reduction in F v /F m resulted from both a decrease in F m and an increase in F 0 (Demmig and Björkman, 1987).…”
Section: Gas-exchange Measurementsmentioning
confidence: 72%
“…The oak species studied were Quercus petraea Liebl As defined by Jones ( , 1985 (Wong et al, 1985;Teskey et al, 1986;Di Marco et al, 1988). A/g increased during drought progression, and reached constant values with a higher water use efficiency (dA/dg) for Q ilex than for Q petraea or Q pubescens under limited water supply.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Electron flow could be maintained at low values of C i through photorespiratory CO 2 , recycling (Osmond et al, 1980;André, 1986). A reduction in the initial slope of F p to F t decline (ie an increase in t 1/2 ) was observed during drought with higher illuminations by Di Marco et al, 1988 (Downton et al, 1988a;Terashima et al, 1988) and in response to water stress in Vitis vinifera, Nerium oleander, Eucalyptus pauciflora and Phaseolus vulgaris (Downton et al, 1988b;Sharkey and Seeman, 1989 In leaves exposed to drought, photoinhibition of photosynthesis by high light treatments was more pronounced, especially in Q petraea and Q pubescens, as has been previously reported for Salix sp leaves (Ögren and Öquist, 1985). The decrease in the apparent quantum yield of net CO 2 assimilation and of F p levels of chlorophyll fluorescence kinetics show that electron transport, and particularly PSII activity were inhibited (Powles, 1984).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Such studies have been made e.g. in wheat (Di Marco et al 1988, Dib et al 1994, Flagella et al 1995, Araus et al 1998, Royo et al 2000, Subrahmanyam et al 2006, Paknejad et al 2007, Sayar et al 2008, Živčák et al 2008, barley (Flagella et al 1998, Li et al 2006, Oukarroum et al 2007, triticale (Hura et al 2007), maize (Selmani andWassom 1991, O'Neill et al 2006), sugarcane (Silva et al 2007), Lolium-Festuca hybrids (Koscielniak et al 2006), potato (Schapendonk et al 1989a, Schapendonk andTonk 1991), or groundnut (Clavel et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The net photosynthetic rate (P N ) measured with some portable gas analysis system has been examined (together with the stomatal conductance (g s ), and sometimes transpiration rate (E) as potential selection marker for the detection of drought tolerance in wheat (Di Marco et al 1988, Subrahmanyam et al 2006, Živčák et al 2008, triticale (Hura et al 2007), maize (Zarco-Perelló et al 2005), potato (Schapendonk et al 1989b), sugar beet (Ober et al 2005), faba bean (Khan et al 2007), or sunflower (Jamaux et al 1997). With the exception of Ober et al (2005), all the above-mentioned studies recommended the P N (or g s ) as a secondary selection marker in breeding for an increased drought tolerance.…”
Section: Introductionmentioning
confidence: 99%